Waiting game : the untold story of the women who served the Tudor queens - Clark, Nicola (Associate lecturer in history) (Pegasus Books, 2025)
Every Tudor Queen had ladies-in-waiting. They were her confidantes and her chaperones. Only the Queen's ladies had the right to enter her most private chambers, spending hours helping her to get dressed and undressed, caring for her clothes and jewels, listening to her secrets. But they also held a unique power. A quiet word behind the scenes, an appropriately timed gift, a well-negotiated marriage alliance were all forms of political agency wielded. The Waiting Game explores the daily lives of ladies-in-waiting, revealing the secrets of recruitment, costume, what they ate, where (and with whom) they slept. --